2019
DOI: 10.1183/13993003.00391-2019
|View full text |Cite
|
Sign up to set email alerts
|

Reducing tuberculosis transmission: a consensus document from the World Health Organization Regional Office for Europe

Abstract: Evidence-based guidance is needed on 1) how tuberculosis (TB) infectiousness evolves in response to effective treatment and 2) how the TB infection risk can be minimised to help countries to implement community-based, outpatient-based care.This document aims to 1) review the available evidence on how quickly TB infectiousness responds to effective treatment (and which factors can lower or boost infectiousness), 2) review policy options on the infectiousness of TB patients relevant to the World Health Organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 91 publications
2
91
0
13
Order By: Relevance
“…A recent review of treatment of LTBI in migrants found that overall poor compliance was key to poor performance (Greenaway et al, 2018). This is also emphasized in the analysis presented in the present study, which clearly demonstrated that cost-effectiveness depends on good compliance; community support is needed to increase compliance (Migliori et al, 2019).…”
Section: Nationality (Country)supporting
confidence: 72%
“…A recent review of treatment of LTBI in migrants found that overall poor compliance was key to poor performance (Greenaway et al, 2018). This is also emphasized in the analysis presented in the present study, which clearly demonstrated that cost-effectiveness depends on good compliance; community support is needed to increase compliance (Migliori et al, 2019).…”
Section: Nationality (Country)supporting
confidence: 72%
“…It is well known that surgical masks can prevent the inhalation of large droplets and sprays but have limited ability to filter submicron-sized airborne particles [8,9]. As SARS-CoV-2 is also embedded in aerosols <5 μm in diameter, it cannot be determined whether they are always effective.…”
Section: Dear Editormentioning
confidence: 99%
“…As SARS-CoV-2 is also embedded in aerosols <5 μm in diameter, it cannot be determined whether they are always effective. However, mask wearing by patients with pulmonary tuberculosis (an airborne infectious disease) has been shown to reduce infectivity to guinea pigs by 56% [9,10]. The surgical mask has also been shown to intercept other human coronaviruses during coughing [11].…”
Section: Dear Editormentioning
confidence: 99%
“…A second similarity is the importance of timely and rapid diagnosis and public awareness for infectious disease control. Long-standing struggles in TB diagnosis represent one of the main reasons for on-going disease transmission in many settings [6,7]. Recent clusters of MDR-TB in Italy and Europe have been linked to diagnostic delays together with inappropriate treatment [8], mainly attributed to the lack of expertise and clinical suspicion on a disease perceived as disappeared.…”
mentioning
confidence: 99%